Role of Nrf2 in Parkinson’s Disease: Toward New Perspectives - Yang, Xin-xing; Yang, Rong; Zhang, Feng (Frontiers in Pharmacology, 2022)
Parkinson’s disease (PD) is one of the most common and chronic degenerative diseases in the central nervous system. The main pathology of PD formation is the progressive loss of dopaminergic neurons in substantia nigra and the formation of α-synuclein-rich Lewy bodies. The pathogenesis of PD is not caused by any single independent factor. The diversity of these independent factors of PD, such as iron accumulation, oxidative stress, neuroinflammation, mitochondrial dysfunction, age, environment, and heredity, makes the research progress of PD slow. Nrf2 has been well-known to be closely associated with the pathogenesis of PD and could regulate these induced factors development. Nrf2 activation could protect dopaminergic neurons and slow down the progression of PD. This review summarized the role of Nrf2 pathway on the pathogenesis of PD. Regulation of Nrf2 pathway might be one of the promising strategies to prevent and treat PD.